2022
DOI: 10.20527/jwm.v9i2.6
|View full text |Cite
|
Sign up to set email alerts
|

Peran Empowering Leadership Dalam Meningkatkan Organizational Citizenship Behavior Melalui Employee Engagement Sebagai Variabel Intervening

Abstract: This study aimed to identify the relationship between empowering leadership and organizational citizenship behavior of employees at Dinas Kesehatan Kabupaten Kerinci through employee engagement. The three variables were constructed and observed the relationship among them. This research utilized quantitative research method using data collection method in the form of a questionnaire then analyzed with Partial Least Square (PLS). The analyzing steps conducted through finding the inner model, outer model and hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…This critical role features responsibility for pedagogical management, with a mandate to monitor the teaching staff and ensure both professional development and proper curriculum development (Leithwood, 2016). Their leadership fosters a sense of citizenship and belonging, as evidenced in studies from Malaysia and Chile, showing a positive relationship between leadership and citizenship behaviour (Hassan et al, 2021;Rosita et al, 2021). Furthermore, research performed in Korea found that coaching leadership influenced organizational citizenship behaviour, mediated by trust and moderated by psychological safety (Bozkurt, 2022).…”
Section: Promoting School Organizational Resilience: Middle Leaders' Tlmentioning
confidence: 99%
“…This critical role features responsibility for pedagogical management, with a mandate to monitor the teaching staff and ensure both professional development and proper curriculum development (Leithwood, 2016). Their leadership fosters a sense of citizenship and belonging, as evidenced in studies from Malaysia and Chile, showing a positive relationship between leadership and citizenship behaviour (Hassan et al, 2021;Rosita et al, 2021). Furthermore, research performed in Korea found that coaching leadership influenced organizational citizenship behaviour, mediated by trust and moderated by psychological safety (Bozkurt, 2022).…”
Section: Promoting School Organizational Resilience: Middle Leaders' Tlmentioning
confidence: 99%
“…The role of leaders is crucial in determining organizational survival through strategic decision-making (Zehnder et al, 2017). Furthermore, Kamal et al (2021) suggest that leaders can demonstrate their competence through effective decisionmaking. The role of leaders needs to be clarified in the decision-making process (Dionisio, 2017).…”
Section: Leader Power and Decision-makingmentioning
confidence: 99%